2021
DOI: 10.1111/ijd.15658
|View full text |Cite
|
Sign up to set email alerts
|

IFN‐α and TNF‐α serum levels and their association with disease severity in Egyptian children and adults with alopecia areata

Abstract: Background Alopecia areata (AA) is an autoimmune skin disease characterized by abnormal levels of several cytokines, such as interferon alpha (IFN-a) and tumor necrosis factor-alpha (TNF-a), which are T-helper type 1 cytokines that have important roles in the pathogenesis of AA. The aim of our study was to correlate circulating IFN-a and TNF-a levels with disease severity, activity, and clinical type in patients with AA and to evaluate the relationship between the two cytokines.Methods We investigated serum IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…A positive correlation between the serum level of TNF and disease severity was reported in the literature [ 40 , 47 ]. Indeed, a study performed by Alzolibani et al [ 24 ] showed the serum level of TNF to be higher in patients with alopecia areata with the severity SALT score ≥ 25% compared to patients with the SALT score < 25%.…”
Section: Cytokines In Alopecia Areatamentioning
confidence: 80%
See 3 more Smart Citations
“…A positive correlation between the serum level of TNF and disease severity was reported in the literature [ 40 , 47 ]. Indeed, a study performed by Alzolibani et al [ 24 ] showed the serum level of TNF to be higher in patients with alopecia areata with the severity SALT score ≥ 25% compared to patients with the SALT score < 25%.…”
Section: Cytokines In Alopecia Areatamentioning
confidence: 80%
“…According to the literature, a positive correlation was reported between the severity of alopecia areata and the serum level of various cytokines including IL-2 [ 25 ], TNF [ 40 ], IL-12 [ 50 ], IL-17 [ 25 , 28 , 48 ], and IL-17E [ 49 ] ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Significantly elevated levels of TNF-α in the serum of AA patients compared to healthy subjects were found (SMD = 2.05, 95% CI 0.98 to 3.13). Among 11 studies that describe TNF-α levels in AA patients and healthy controls, eight studies describe higher levels of TNF-α in AA patients 11,23,25,27-30, 32 , and no significant difference was seen in three studies 15,18,31 . Forest plots of TNF-α, IL-6, and IL-10 are shown in Figures 2 and 3and…”
Section: Resultsmentioning
confidence: 99%